2022
DOI: 10.25122/jml-2022-0157
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity-related sarcopenia: a review

Abstract: A body of literature supports the postulation that a persistent lipid metabolic imbalance causes lipotoxicity, “an abnormal fat storage in the peripheral organs”. Hence, lipotoxicity could somewhat explain the process of sarcopenia, an aging-related, gradual, and involuntary decline in skeletal muscle strength and mass associated with several health complications. This review focuses on the recent mechanisms underlying lipotoxicity-related sarcopenia. A vicious cycle occurs between sarcopenia and ectopic fat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Capillaries, which are crucial for nutrient transport to cells, show a correlation with health-related indicators. Recent studies have reported an inverse relationship between body fat mass and capillary diameter, underscoring the importance of reducing body fat through continuous exercise therapy [30]. However, exercise therapy poses a risk of triggering cardiovascular events in high-risk elderly individuals [31], making sustained implementation challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Capillaries, which are crucial for nutrient transport to cells, show a correlation with health-related indicators. Recent studies have reported an inverse relationship between body fat mass and capillary diameter, underscoring the importance of reducing body fat through continuous exercise therapy [30]. However, exercise therapy poses a risk of triggering cardiovascular events in high-risk elderly individuals [31], making sustained implementation challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In obese status, the secretion of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β) and interleukin-6 (IL-6) from adipocytes and macrophages, triggers a cascade of intracellular signaling in muscle cells, followed by increasing the transcriptional activities of nuclear factor-kappa B (NF-κB) and forkhead box O (FoxO) family, especially FoxO3a, finally promotes the gene expression of MAFbx and MuRF1 and accelerates proteolysis [13][14] . In addition, obesity also suppresses muscle protein synthesis via inhibiting the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (also called Akt) pathway [15] .…”
Section: Introductionmentioning
confidence: 99%